Integrated teaching of inorganic chemistry with modern information technologies in higher education institutions - Jiemuratova Aynura Amangeldievna; Pardayev Ulug'bek Xayrullo o'g'`li; Bobojonov Jamshid Shermatovich (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Inorganic chemistry, a fundamental discipline in the chemical sciences, often presents challenges for both students and educators due to its abstract nature and complex concepts. This article explores the integration of modern information technologies to improve the teaching and learningexperience of inorganic chemistry in higher education institutions. Leveraging digital tools such as virtual laboratories, multimedia resources, interactive simulations, and online platforms, educators can provide students with dynamic and immersive learning experiences. By incorporating these technologies, instructors can illustrate abstract concepts more effectively, facilitate active engagement, and offer personalized learning opportunities. These tools enable students to access educational materials beyond the confines of the traditional classroom, fostering self-directed learning and enhancing overall comprehension.